Seed germination of three species of Bignoniaceae trees under water stress (Revista Ciência Agronômica, 2021)
Seed germination and seedling development are strongly infl uenced by water availability and temperature, therefore, knowledge ofthe tolerance limits against these factors can generate subsidies to improve the multiplication and conservation strategies of native tree species. Thisstudy evaluates the effects of water stress on the germination of Tabebuia roseoalba, Handroanthus chrysotrichus, and H. impetiginosus seeds at twotemperatures. Germination was performed on paper rolls moistened with polyethylene glycol (PEG 6000) solutions for the osmotic potentials of 0(water); -0.05; -0.10; -0.15; -0.20; -0.30; -0.40; -0.60; -0.80 and -1.00 MPa. Germination tests were conducted at 25 and 30 °C, under 8 h photoperiod.Statistical analyses for each studied species followed a randomized complete block design, in a 2 × 10 split-plot scheme (plots - two temperatures andsubplots – ten water potentials). The percentage of germination and normal seedlings, as well as the germination speed and synchronization indexes,were evaluated. The germination of T. roseoalba, H. chrysotrichus, and H. impetiginosus seeds decreased with increasing water defi cit and at higherrates when associated with higher temperatures. The results demonstrate that the species sensitivity to water defi cits induced by PEG 6000, increaseswith rising temperatures. T. roseoalba and H. chrysotrichus exhibited a germination tolerance range between -0.80 and -1.00 MPa. Furthermore, H.impetiginosus is more sensitive and displayed a tolerance range between -0.60 and -0.80 MPa.